DEVELOPMENT OF COGNITIVE INDEPENDENCE OF STUDENTS IN GAME ACTIVITIES (Pedagogy of Higher and Secondary Education, 2001)
The article deals with the problems of the development of cognitive independence of teenagers in the playing activity the mathematics lessons.